Respuesta :

The answer to the question is true.


Answer:

True

Step-by-step explanation:

Given expression is 125[tex]x^{3} + 216[/tex]

Now we have to write 125 and 216 as a power of cube.

125 = 5*5*5 = [tex]5^{3}[/tex]

Similarly, we can write

216 = 6*6*6 = [tex]6^{3}[/tex]

We can rewrite the given expression as

[tex]5^{3} x^{3} + 6^{3}[/tex]

We know [tex](ab)^{3} = a^{3} b^{3}[/tex] Using the power property rule.

[tex](5x)^{3} + 6^{3}[/tex]

Which is the sum of cubes.

Therefore, the answer is True.